Redes clientelísticas em pequenas cidades do Piauí: as trocas políticas "assimétricas" entre lideranças políticas e eleitores nas eleições de 2016-2018 - Vasconcelos, José Cláudio da Silva (2022)
This research investigates the network of asymmetric/clientelistic political exchanges between state leaders (state and federal deputies) and local leaders (mayors and councilors) and the most economically vulnerable voters in the 2016-2018 elections in the small towns of Piauí. The main objective of the study was to demonstrate the relationship of citizenship/autonomy and clientelism/dependence existing between these political leaders and voters who, by returning the favors received with their votes, become dependent on certain votes (state deputy and federal deputy), but exercise their autonomy when voting for other positions (governor, senator and president). Thus, the concept of clientelism is adopted as a dialectical phenomenon, demonstrating both the relationship of personal dependence and citizenship that exists between voters and local leaders. There is another objective revolving around the main one, consisting in observing how the coexistence of clientelism and the modern state, in which clientelism survives, adjusting to the new structures of modern societies. There was also a counterpoint to patrimonialism, in addition to emphasizing that Brazilian society is heteroclite, contradicting this theory, because instead of eliminating “backwardness”, during the consolidation of the country's modernization process, it made functional in this new order. The research is a case study in which the qualitative method was applied, using the techniques of in-depth interviews and the realization of focus groups. The sample is composed by four cities, each one of them representing a mesoregion of Piauí: Cocal (North Mesoregion of Piauí), Campo Maior (North Central Mesoregion of Piauí), Oeiras (Southeast Mesoregion of Piauí) and São Raimundo Nonato (Southwest Mesoregion of Piauí). As a basic theoretical framework, refer to Santos, Souza, Oliveira, Bahia, D´Avila Filho, Vianna and Faoro. As a result, it became evident that voters, when exercising their right to vote, make in a dialectical way: clientelistic and citizen, that is, they act as dependent individuals and at the same time, as autonomous; state and local leaders create and maintain mutual political agreements so that both continue to survive politically, which means winning elections. It was also found that clientelism does not remain confined to societies seen as emerging, it also coexists in societies of advanced industrialization, where capitalism has fully developed. Brazil is a case of modernization that does not follow the classic model, resulting in a society in which the “old” and the “new” feed off each other, in a symbiotic relationship.